Beyond the Limits of Oxygen: Effects of Hypoxia in a Hormone-Independent Prostate Cancer Cell Line. (12th September 2013) - Mamede, A. C.; Abrantes, A. M.; Pedrosa, L.; Casalta-Lopes, J. E.; Pires, A. S.; Teixo, R. J.; Gonçalves, A. C.; Sarmento-Ribeiro, A. B.; Maia, C. J.; Botelho, M. F.
Abstract : Prostate cancer (PCa) has a high incidence worldwide. One of the major causes of PCa resistance is intratumoral hypoxia. In solid tumors, hypoxia is strongly associated with malignant progression and resistance to therapy, which is an indicator of poor prognosis. The antiproliferative effect and induced death caused by doxorubicin, epirubicin, cisplatin, and flutamide in a hormone-independent PCa cell line will be evaluated. The hypoxia effect on drug resistance to these drugs, as well as cell proliferation and migration, will be also analyzed. All drugs induced an antiproliferative effect and also cell death in the cell line under study. Hypoxia made the cells more resistant to all drugs. Moreover, our results reveal that long time cell exposure to hypoxia decreases cellular proliferation and migration. Hypoxia can influence cellular resistance, proliferation, and migration. This study shows that hypoxia may be a key factor in the regulation of PCa.